Climate-Smart Agriculture (CSA): Training Manual - Bhusal, Aastha; Khatri, Laxman; Bhandari, Bharat; Sherpa, Lakpa; Neupane, Grishma (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Nepal is one of the most vulnerable countries to the negative effects of climate change. It has been actively implementing various programmes related to climate change management since it signed a treaty for the United Nations Framework Convention on Climate Change (UNFCCC). Nepal has prepared a National Adaptation Programme of Action (NAPA) in 2010 and implemented several climate change adaptation projects. Similarly, in 2011, Nepal has developed the National Framework on Local Adaptation Plan of Action (LAPA) in order to integrate the climate change related issues in the local development plan. The Government of Nepal (GoN) has endorsed the climate change policy, 2011. The National Agriculture Policy, 2004, Agriculture Development Strategy (ADS) and 15th Five-year Plan have also tried to address climate change related issues at policy level. Agriculture sector has been highly affected by climate change induced risks and challenges. Thus, it is utmost important to reduce the impact of climate change by building the agriculture system more resilient through promotion of various climate smart technologies and practices. In this regard, there’s an urgent need to develop and disseminate relevant technologies, strengthen the capacities of farmers through providing technical assistance for the adoption of the technologies and implement various programmes to improve the livelihoods of farming communities. The Gandaki province has varied agro-ecological region hence has huge potential for diverse agriculture and livestock commodities however it is equally vulnerable to climatic induced risks. Considering this, Ministry of Land Management, Agriculture and Cooperative (MoLMAC), Gandaki Province, has been implementing Chief Minister Climate Friendly Model Agriculture Village Programme (CMCFMAVP) since 2018 in order to increase agricultural production and ensure food security in the face of climate change. The CMEFMAVP has established 87 model villages in 85 municipalities. In these villages, various programmes have been implemented in order to promote climate-smart agriculture (CSA) technologies and practices for minimizing the negative impacts of climate change and increasing the adaptive capacity of the farming communities. In this regard, the MoLMAC, Gandaki province and Local Initiatives for Biodiversity, Research and Development (LI-BIRD) has signed a MoU in order to implement climate change related programmes, disseminate various technologies and provide capacity building trainings. In order to make these training programme more effective, MoLMAC and LI-BIRD have jointly published a ‘Climate-Smart Agriculture Training Manual’. The training manual is expected to help field level technician to effectively organize a five-days training programme on climate change. The contents covered will help them understand the concept of climate change, its impacts, different climate-smart agriculture technologies and practices and deliver the same. The knowledge generated through this training manual is expected to be useful and applied at farmers’ level.